Effectiveness of self-management programs for people with osteoarthritis of the knee - Coleman, Sophie (Curtin University, 2011)
The effectiveness of a new disease-specific self-management program for people with osteoarthritis of the knee was evaluated in two randomised controlled trials. Compared to a no intervention control, the program was found to be effective resulting in improvements in pain, function and quality of life. Moreover, compared to a generic arthritis self-management program, the disease specific program resulted in superior improvements in pain, physical function and general health, particularly in the short term.